Gugatan Class Action dalam Penegakan Hukum Lingkungan di Indonesia - Erlina B (KEADILAN PROGRESIF, 2010)
Class Action in Indonesia to be see in Environmental Management Law No.23/1997and have amanded Protection and Management of Environment Law No. 32/2009,on the followed by Forestry Law No.41/1999, and so on. In Indonesia, there are 3(three) cases that attract attention: First, Kapak LPG Lawsuit, decision requets ofthe plaintiff is won, but Jakarta Province Court decision was rejected. Second, thevictim of consumer of railways in Brebes. In this case requets of the plaintiff claimwas granted is won. Third, Flooding lawsuit in Jakarta year 2002, in this case requetsof the plaintiff was rejected, on the based of Indonesian Presiden, Governor of Jakartaand Governor West Java is not responsible for flooding in Jakarta, but the mayor infive regions of Jakarta Province under Law Local Governance No.22/1999.